Migration of Classic Plot (Ch. Perrault’s “The Blue Beard”) in Modern French Literature of 21st Century (A. Nothomb’s “The Blue Beard”) - T. V. Nuzhnaya; K. V. Kovalchuk (Научный диалог)
The author analyzes the topical in modern literary criticism issue of classical plots migration in modern French literature of the 21st century. Results of a comparative analysis of the principles and techniques of the plot construction of the tale by Charles Perrault “Blue Beard” (1697) and of the novel by Amélie Nothomb “Blue Beard” (2012) are presented. It is shown that classical works become part of the development of modern literature, fit into the context of everyday life of our time and correspond to the poetics of the new text. Analysis of the composition and the figurative system of Amélie Nothomb’s novel allows to identify its main differences from the fairy tale by Charles Perrault, linked with the radical change of the genre of the narrative. French writer significantly expands the storyline, while maintaining the canvas of the original fairy tale. It is noted that the focusing on adventure, saturation with unusual turns in the development of events and mystical denouement allow to conclude that the investigated novel belongs to the genre of “middle literature.” The authors of the article prove that remakes of classical plots in the literature of the 21st century not only do not detract from the dignity of new genre forms of narration, but also reflect the specifics of the modern context within the continuity of literary traditions.